Clinico-etiological Profile of Seizure Disorder among Adults Admitted to Tertiary Care Hospital of Nepal - Rayamahji, Parash; Karn, Ragesh; Gajurel, Bikram P; Rajbhandari, Reema; Ojha, Rajeev; Agrawal, Jagadish P (Journal of Institute of Medicine Nepal, 2019)
Introduction: Seizures beginning in the adult life require special attention as regards to their etiology because these are likely to be due to an identifiable cause. Understanding the trend in prevalence of various etiology of seizure will help in formulation of diagnostic protocol and might help to reduce the cost of investigations. In this retrospective study, we, therefore, aimed to assess etiology and clinical profile of adult onset seizures. Methods: This was a retrospective study done at Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal. We included patients of both sexes and age > 18 years old admitted to neurology ward with seizure disorder and excluded the patients who suffered from unprovoked seizure and epilepsy. Our study variables included demographic profile of patients, co-morbidities, clinical features, laboratory investigation, neuro-imaging, EEG and drugs. Results: Among 26 patients, 3 (11.5%) had hyponatremia, 2(7.7%) had intra-cranial space occupying lesion, 12(46.2%) had neurocysticercosis (NCC), 1 (3.8%) had opioid withdrawal, 1 (3.8%) had alcohol withdrawal, 1 (3.8%) had stroke, 1 (3.8%) tuberculoma and in 5 (19.2%) patients no underlying cause was found. Conclusion: NCC was the most common cause of seizure disorders among adults. Even after huge development in laboratory, neuroimaging and neurophysiology testing, in as much as 19.2% patients, no etiology could be found.